The influence of ligament biomechanics on proximal junctional kyphosis and failure in patients with adult spinal deformity - Micah Blais; Bahar Shahidi; Brad Anderson; Eli O'Brien; Courtney Moltzen; Tina Iannacone; Robert K. Eastlack; Gregory M. Mundis Jr (JOR Spine, 2023)
Abstract Purpose It is unknown whether the biomechanics of the posterior ligamentous complex (PLC) are impaired in individuals undergoing surgery for adult spinal deformity (ASD). Characterizing these properties may improve our understanding of proximal junctional kyphosis (PJK; defined as proximal junctional angle [PJA] of >10 deg from UIV‐1 to UIV + 2), as well as proximal junctional failure (PJF; symptomatic PJK requiring revision). The purpose of this prospective observational study is to compare biomechanical properties of the PLC in individuals with ASD who do, and do not develop PJK or PJF within 1 year of spinal fusion surgery. Methods Intraoperative biopsies of PLC were obtained from 32 consecutive patients undergoing spinal fusions for ASD (>4 levels). Ligament peak force, tensile stress, tensile strain, and elastic modulus (EM) were measured with a materials testing system. Biomechanical properties and tissue dimensions were correlated with age, gender, BMI, vitamin D level, osteoporosis, sagittal alignment, PJA and change in PJA preoperatively, within 3 months, and at 1 year postoperatively. Results Longer ligaments were associated with greater PJA change at 3 months (p = 0.04), and thinner ligaments were associated with greater PJA change at 1 year (r = 0.57, p = 0.01). Greater EM was associated with greater PJA at both 3 months and 1 year (p = 0.03). Five participants had a change in PJA of >10 1 year postoperatively, and three participants demonstrated PJF. EM was significantly higher in individuals who required revision surgery (p = 0.003), and ligament length was greater (p = 0.03). Preoperative sagittal alignment was not related to incidence of revision surgery (p > 0.10). Conclusions The biomechanical properties of the PLC may be associated with higher risk for proximal failure. Ligaments that are longer, thinner, and less elastic are associated with higher postoperative PJA. Furthermore stiffer EM of the ligament is associated with the need for revision surgery.